Sources and seasonality of atmospheric methanol based on tall tower measurements in the US Upper Midwest - L. Hu (Atmospheric Chemistry and Physics, 2011)
We present over one year (January 2010–February 2011) of continuous atmospheric methanol measurements from the University of Minnesota tall tower Trace Gas Observatory (KCMP tall tower; 244 m a.g.l.), and interpret the dataset in terms of constraints on regional methanol sources and seasonality. The seasonal cycle of methanol concentrations observed at the KCMP tall tower is generally similar to that simulated by a global 3-D chemical transport model (GEOS-Chem, driven with MEGANv2.0 biogenic emissions) except the seasonal peak occurs ~1 month earlier in the observations, apparently reflecting a model underestimate of emission rates for younger versus older leaves. Based on a source tracer approach, which we evaluate using GEOS-Chem and with multiple tracers, we estimate that anthropogenic emissions account for approximately 40% of ambient methanol abundance during winter and 10% during summer. During daytime in summer, methanol concentrations increase exponentially with temperature, reflecting the temperature sensitivity of the biogenic source, and the observed temperature dependence is statistically consistent with that in the model. Nevertheless, summertime concentrations are underestimated by on average 35% in the model for this region. The seasonal importance of methanol as a source of formaldehyde (HCHO) and carbon monoxide (CO) is highest in spring through early summer, when biogenic methanol emissions are high but isoprene emissions are still relatively low. During that time observed methanol concentrations account for on average 20% of the total CO and HCHO production rates as simulated by GEOS-Chem, compared to 12% later in the summer and 12% on an annual average basis. The biased seasonality in the model means that the photochemical role for methanol early in the growing season is presently underestimated.